2012
DOI: 10.1007/s10877-012-9420-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of propofol and sevoflurane on QT interval during anesthetic induction

Abstract: There have been conflicting reports on whether propofol prolongs, shortens, or does not change QT interval. The aim of this study was to determine the effect of target-controlled infusion (TCI) of propofol on heart rate-corrected QT (QTc) interval during anesthetic induction. We examined 50 patients undergoing lumbar spine surgery. Patients received 3 μg/kg of fentanyl and were randomly allocated to one of the following 2 groups. Group S patients received 5 mg/kg of thiamylal followed by sevoflurane, 5 % at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 23 publications
0
30
1
Order By: Relevance
“…There have been conflicting reports regarding whether propofol sedation lengthens, shortens, or does not affect QT intervals. Kim et al (21) reported lengthening of the QTc intervals by propofol administration, whereas Oji et al (22) reported shortening of the QTc interval. Whyte et al (13) found no effect of propofol on QTc interval.…”
Section: Discussionmentioning
confidence: 99%
“…There have been conflicting reports regarding whether propofol sedation lengthens, shortens, or does not affect QT intervals. Kim et al (21) reported lengthening of the QTc intervals by propofol administration, whereas Oji et al (22) reported shortening of the QTc interval. Whyte et al (13) found no effect of propofol on QTc interval.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been conflicting reports on the QTcD-prolonging effects of desflurane [1,5]. Our previous studies showed that propofol or thiamylal with sevoflurane does not affect QTD in similar study populations [2,14]. Altogether, these studies suggest that co-existing cardiac disease could influence QTcD during desflurane anesthesia induction.…”
Section: Discussionmentioning
confidence: 94%
“…We chose to use average values from the 12-lead ECG because of inter-lead variations in the QT interval [13]. Moreover, we previously found that propofol shortens the QTc interval [6,14], and an injection of propofol counteracted the QTc interval prolongations associated with sevoflurane anesthesia induction [2] and antiemetic dose of droperidol [15]. Sympathetic stimulation is one of the factors interfering with the QTc interval.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia was induced with target-controlled infusion (TCI) of propofol and remifentanil. The target predicted plasma concentration of propofol was 3.0 μg/mL [18]. This predicted plasma propofol concentration was kept stable for 3 minutes and then remifentanil TCI begun.…”
Section: Anesthesia Protocolmentioning
confidence: 94%